More effort with less pay: On information avoidance, optimistic beliefs, and performance - Steffen Huck; Nora Szech; Lukas M. Wenner (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
Recent behavioral models argue in favor of avoidance of instrumental information. We explore the role of information avoidance in a real-effort setting. Our experiment offers three main results. First, we confirm that preferences for avoidance of instrumental information exist, studying information structures on performance pay. Second, information avoiders outperform information receivers. This result holds independently of effects of self-selection. Third, the findings support theories on information avoidance that favor an optimistic belief design rather than theories that rationalize such behavior as a way to mitigate selfcontrol problems. This suggests that coarse information structures lead agents to distort their beliefs away from the objective prior.
Keywords: D83; D84; J31; M52; 330; optimal expectations; belief design; performance; real effort task; coarse incentive structures; workplace incentives